The Specific Judo Training Program Combined With the Whole Body Cryostimulation Induced an Increase of Serum Concentrations of Growth Factors and Changes in Amino Acid Profile in Professional Judokas - Jaworska, Joanna; Laskowski, Radoslaw; Ziemann, Ewa; Zuczek, Klaudia; Lombardi, Giovanni; Antosiewicz, Jedrzej; Zurek, Piotr (Frontiers in Physiology, 2021)
The aim of this study was to evaluate the effect of the specific training program supported by 10 sessions of whole body cryostimulation on changes in growth factors concentration, amino acids profile, and motor abilities among professional judokas. Finally, twelve athletes took part in the study. They were randomly assigned into either a cryostimulation group (CRY, n= 6) or a control group (CON, n= 6). During the applied judo training program participants from the CRY group performed 10 cryo-sessions (3 min at a temperature of -110°C) and the CON group had passive rest. Anthropometric measurements, strength test, the Specific Judo Efficiency Test (SJET) were assessed two days before and after the 2-week judo training program. Blood samples were collected at rest condition, 1h after the first and the second SJET, and as well 1h after the first and the last cryo-session to establish growth factors and amino acid concentrations. Lactate level was measured before, immediately after and 1h after the first and the second SJET. The applied intervention resulted in the significant increase of resting serum brain-derived neurotrophic factor (from 10.23±1.61 ng∙ml-1 to 15.13±2.93 ng∙ml-1; p= 0.01) and insulin-like growth factor 1 (IGF-1; from 174.29±49.34 pg∙ml-1 to 300.50±43.80 pg∙ml-1; p= 0.00) in the CRY group. Also, a different response was registered 1h directly post SJET in the CRY group (significant increase of IGF-1, interleukin 15 and irisin: p=0.01; p=0.00; p=0.03). Additionally, the significant proline and leucine concentrations in the CRY group were obtained. Athletes’ performance outcomes remained unchanged in both groups. Positive changes induced by the whole intervention were noted not directly after cryo-session but they were visible in response to specific training workload. The increase of growth factors and the improvement of amino acid profile (proline and leucine) contributed to maintain the high level of muscle function.